Nicolaou, Anna - (:unkn) unknown (My University, 2026)
Anna Nicolaou is an English Language Instructor at the Language Centre of the Cyprus University of Technology (CUT). She holds a Ph.D. from Trinity College Dublin (Ireland), focusing on Intercultural Education and Global Competence learning through Virtual Exchange, a Master's degree in English Language Studies and Methods from the University of Warwick (United Kingdom) and a Bachelor’s degree in English Language and Literature from the National and Kapodistrian University of Athens (Greece). Prior to joining the Cyprus University of Technology, she worked for many years as a Senior Lecturer in private higher education. At undergraduate level, she teaches English for Academic and Specific Academic Purposes. At postgraduate level she teaches Second Language Acquisition and Research Methods in Applied Linguistics. Her research interests include Intercultural Education, Virtual Exchange, Multilingualism, Internationalization, Methodology of Teaching English as a Foreign/Second Language, Computer Assisted Language Learning, 21st Century Learning, Ecology, as well as Immersive Technologies in Language Learning. She has published scientific articles in internationally acclaimed journals and has participated in research programs and academic conferences.
Keywords: Intercultural Education; Immersive Technologies; Virtual Exchange; Internationalization; Technology-enhanced Learning; arts; social